Investigating faculty motivation and its connection to faculty work-life balance: Engaging public service motivation to explore faculty motivation. (1st October 2020) - Pautz, Michelle C.; Vogel, Morgan D.
ABSTRACT: Discussions of work-life balance challenges among members of the academy abound and this study contributes to those conversations by taking a step back and investigating faculty motivation. We contend that understanding the motivation of faculty members and their views of work are necessary as we engage in work-life balance conversations. More specifically, we integrate the public service motivation (PSM) literature to study the motivation of faculty in public administration and political science programs in this exploratory study. We find that faculty in this study are motivated by their desire to contribute meaningfully to society, by an interest in working with students and the fulfillment that comes with teaching, and by an opportunity for intellectual stimulation and autonomy that comes with being a member of the academy. These insights are useful because they help us understand the levels of intrinsic motivation among faculty and the resulting tendencies to experience stress, fatigue, and burnout. Undoubtedly more research in this area is needed, but we posit that understanding faculty motivation is an essential piece of the conversation about faculty work-life balance.